Intersphincteric Resection and Coloanal Anastomosis in Treatment of Distal Rectal Cancer. (29th May 2012) - Cipe, Gokhan; Muslumanoglu, Mahmut; Yardimci, Erkan; Memmi, Naim; Aysan, Erhan
Abstract : In the treatment of distal rectal cancer, abdominoperineal resection is traditionally performed. However, the recognition of shorter safe distal resection line, intersphincteric resection technique has given a chance of sphincter-saving surgery for patients with distal rectal cancer during last two decades and still is being performed as an alternative choice of abdominoperineal resection. The first aim of this study is to assess the morbidity, mortality, oncological, and functional outcomes of intersphincteric resection. The second aim is to compare outcomes of patients who underwent intersphincteric resection with the outcomes of patients who underwent abdominoperineal resection.